Perbedaan Jumlah Eritrosit Sebelum dan Sesudah Donor Darah di Rumah Sakit Muhammadiyah Mardhatillah Randudongkal Pemalang - Anggia Lestari; Yunita Rusidah (Jaringan Laboratorium Medis, 2026)
Blood donation is a humanitarian activity that plays an important role in meeting national blood supply needs; however, it may cause temporary changes in hematological parameters, including erythrocyte count. This study aimed to analyze the difference in erythrocyte count before and 60 minutes after blood donation among voluntary donors. This research used a pre-experimental quantitative design with a One Group Pretest–Posttest approach. A total of 39 voluntary donors were selected using a purposive sampling technique. Erythrocyte counts were measured using an automated hematology analyzer before and 60 minutes after blood donation. Data analysis began with the Shapiro–Wilk normality test and homogeneity test, which showed that the data were normally distributed and homogeneous (p > 0.05), followed by a Paired Sample t-Test. The results showed that the mean erythrocyte count decreased from 4.71 ± 0.49 million/µL before donation to 4.46 ± 0.51 million/µL at 60 minutes after donation. Statistical analysis indicated a significant difference between pre- and post-donation erythrocyte counts (p < 0.001). In conclusion, blood donation causes a significant decrease in erythrocyte count within the first hour after donation as an acute physiological response to blood loss. These findings highlight the importance of hematological monitoring and post-donation recovery education for donors.